Oxidized galectin-1 reduces lipopolysaccharide-induced increase of proinflammatory cytokine mRNA in cultured macrophages - Yukie Kogawa; Kou Nakajima; Kenichi Sasaguri; et al (Dove Medical Press, 2011)
Yukie Kogawa1, Kou Nakajima1, Kenichi Sasaguri1, Nobushiro Hamada2, Haruhisa Kawasaki3, Sadao Sato1, Toshihiko Kadoya4, Hidenori Horie51Department of Orthodontics, 2Department of Oral Microbiology, Kanagawa Dental College, Yokosuka; 3Keio University, Kanagawa; 4Maebashi Institute of Technology, Maebashi; 5Research Center of Brain and Oral Science, Kanagawa Dental College, Yokosuka, JapanBackground: Periodontitis is prevalent in older humans. Limiting the inflammation associated with periodontitis may provide a therapy for this condition, because Gram-negative bacteria expressing lipopolysaccharide (LPS) have a key role in initiation of inflammation by activating macrophage functions. Because oxidized galectin-1 regulates macrophage functions in other systems, we sought to establish whether this galectin-1 mRNA is expressed in the oral cavity, and whether it could dampen LPS-induced macrophage activation in vitro.Methods: Using the reverse transcriptase polymerase chain reaction (RT-PCR), we measured galectin-1 mRNA expression to clarify its localization to rat gingival tissues and studied the effect of Porphyromonas gingivalis challenge on galectin-1 expression. Next, we tested the effects of adding oxidized galectin-1 to cultured LPS-activated peritoneal macrophages on mRNA expression of proinflammatory factors by RT-PCR and real-time RT-PCR.Results: We established that galectin-1 mRNA is expressed in gingival tissues and also showed that galectin-1 mRNA was significantly increased by challenge with P. gingivalis, indicating that galectin-1 may regulate oral inflammation. On the other hand, LPS 100 ng/mL in serum-containing medium induced macrophages to upregulate mRNA associated with a proinflammatory response, ie, interleukins 1β and 6, and inducible nitric oxide synthase. We showed that application of 0.1–10 ng/mL of oxidized galectin-1 to LPS-treated macrophages reduced the intense LPS-induced increase by serum in proinflammatory mRNA expression in a concentration-dependent manner. Furthermore, application of oxidized galectin-1 10 ng/mL to LPS-treated macrophages in serum-free medium also showed a similar effect on LPS activity.Conclusion: Oxidized galectin-1 restricts the proinflammatory actions of LPS, and this protein could limit the negative effects of inflammation.Keywords: periodontitis, inflammation, macrophage, lipopolysaccharide, galectin-1, proinflammatory factors